Influence Of Urban- Industrial Growth In Haldia Town, West Bengal (International Journal of Food and Nutritional Sciences, 2022)
Economic development of the country is depending on mainly industrial growth and development. The new setup city are constantly undergoing due to urban-industrial development. Haldia, a port cum industrial town is the secondary employment sector which involves large number of peoples is engage to the various industrial purposes. The Haldia port town grows in early 1970s and popular industrial town in West Bengal. Now The Haldia town is the fastest growing port of the Eastern India. The Haldia port town is situated in the Haldi river bank, this place is nearest of the Bay of Bengal Sea. Kolkata and Kharagpur are join to Haldia by the south-eastern railway. Kolkata and Howrah are join by the national high way no 46. The land surface is plane and soil condition is very eliding. The weather condition is very comfortable. Good location advantage, better connectivity, large number of educated people and different facilities are improve for rapid industrial changes have been seen within 25 years. The development has helped the economic growth of the region and it also related with the formulation of urbanization in Haldia town. Now a days the economic condition, this type of study is very helpful to understand that how this growth of industry and urbanization has helped the economy of the region.